Preparing industry leaders: an evaluation of former AFA participants’ workplace skills - Svacina, Leslie (Kansas State University, 2009)
For more than 10 years Agriculture Future of America (AFA) has been helping college students from around the country prepare for careers in the food and agriculture industry. Over time the organization has received a lot of positive feedback from both participating students and employers. The feedback has led the organization to believe there is an “AFA Advantage,” where participants have an advantage over their peers when entering the workforce due to their AFA involvement. The purpose of the thesis was to determine if there is an “AFA Advantage,” by measuring former participants’ workplace skill sets, as determined by agribusiness employers in a previous study. To accomplish this purpose, two sub-objectives were evaluated, measuring the skill competencies of former AFA participants participating in a (1) self assessment and (2) comparison with peers, who were not involved in AFA. The analysis is based on survey results from former AFA participants. The conceptual model established examined if there was a relationship between AFA, college and the skills desired by agribusiness employers. The skills measured include interpersonal communication skills, critical thinking skills, knowledge of general business practices, quantitative analysis skills, cultural/gender awareness, and oral presentation skills. Through this research, it was determined that there is an “AFA Advantage.” Data shows evidence that former participants do attribute AFA to helping them develop skills for the workplace. In fact, as the years of AFA participation increased, individuals tended to agree more that AFA contributed to their workplace skill competencies.
Keywords: Agriculture; Assessment; Career; College; Leadership; Skills; Business Administration, Management (0454); Education, Agricultural (0517); Education, Higher (0745)